The role of social closeness in pure coordination games - Jiang, Yunchao (2024)
Theoretical and empirical studies suggest that individuals can coordinate on focal points in pure coordination games without communication, and their behaviours are influenced by personal and game structure factors. This research seeks to explain how social closeness influences player behaviour in pure coordination games. We propose a hierarchical structure of mutual knowledge as the mechanism through which players select a type of mutual knowledge to rely on for salience identification. Additionally, we present the design of a three-phase experiment, presenting seven expected results of treatment and within-treatment effects. These results, if observed, would provide support for our theoretical hypotheses.